Hypothermia Mitigates Renal Fibrosis Through the Upregulation of PGC-1α After Ischemia–Reperfusion Injury - Dabi Kim; Suyeon Han; Hyunsu Choi; Yoon-Kyung Chang; Dae Eun Choi (Biomedicines)
Background: Hypothermia has been previously reported to ameliorate acute renal injury induced by ischemia–reperfusion injury (IRI). However, its protective effects against subsequent renal fibrosis remain unclear. Objectives: The aim of this study was to determine whether hypothermia provides protection against renal ischemia–reperfusion injury (IRI), and to elucidate the molecular mechanisms involved. Methods: We used a model of renal fibrosis after ischemia–reperfusion injury in mice. C57BL/6 mice were divided into the following groups: control mice and ischemia–reperfusion injury mice (at 37 °C and at 32 °C). Their kidneys were harvested on day 1, day 3, and day 7 after IRI. The molecular mechanisms were evaluated. Results: The blood urea nitrogen (BUN) levels, serum creatinine (s-Cr) levels, and the histologic renal injury scores were significantly lower in the 32 °C IRI group than in the 37 °C ischemia–reperfusion injury group. In the hypothermic IR group, TGF-β and α-SMA were significantly decreased, while the PGC-1α level was significantly increased. Cold preparation increased the PGC-1α levels in HK2 cells. In TGF-β-treated HK2 cells, cold preparation decreased α-SMA and collagen IV levels. In addition, siPGC-1α in HK2 cells increased α-SMA and collagen IV, despite cold preparation. Conclusions: Hypothermia attenuates renal function deterioration and renal fibrosis in renal IRI mice kidneys. PGC-1α may play a role in hypothermic protection in renal fibrosis after IRI.